Analisis Efisiensi Produksi dan Pemasaran Jambu Mete di Kabupaten Flores Timur - Yusuf Yusuf; Masyhuri Masyhuri; M Maksum (Agro Ekonomi, 1999)
Cashew fruit (Anacardium Occidentale.L) is one of important annual industrial plants. The commodity is very prospective in international market.